A comparative study of the outcome of unilateral versus bilateral internal anal sphincterotomy in treatment of chronic anal fissure - Partha Pratim Mandal; Shivaji Mandal; Chowdhury, Debayan (Asian Journal of Medical Sciences, 2024)
Background: Gold standard treatment for chronic anal fissure is lateral internal sphincterotomy. Bilateral internal sphincterotomy (BIS) as a treatment option for chronic anal fissure has not been evaluated. Aims and Objectives: The aims and objectives of the study are to compare the efficacy of unilateral versus bilateral internal anal sphincterotomy in treatment of chronic anal fissure. Materials and Methods: Study design: A prospective randomized comparative study. Study area: Patients coming to General Surgery outpatient department at College of Medicine and Sagore Dutta Hospital with chronic anal fissure. Study period: July 2022 to December 2023 (18 months). Sample Size: 100 patients. Study Group: Group A=Patients who had undergone unilateral internal sphincterotomy (UIS)=50 patients and Group B=Patients who had undergone BIS=50 patients. Results: 2 (4%) patients in Group A and 3 (6%) patients in Group B developed incontinence for flatus postoperatively. No patients in either group developed incontinence for stools. The Mean Fissure Healing Time (Mean±SD) (Weeks) post-sphincterotomy was 4.32±0.91339 in Group A and 2.66±0.65807 in Group B. There were 6 cases of recurrence in the unilateral sphincterotomy group. Second surgery was needed in 4 patients who underwent unilateral sphincterotomy. Conclusion: As compared to UIS, BIS results in a faster healing of chronic anal fissure, with no increase in incontinence, decreased pain score, and less recurrence rates.